Intoxicação experimental por monensina em búfalos e bovinos Experimental monensin poisoning in water buffaloes (Bubalus bubalis) and cattle - Daniela B. Rozza; André M. Ribeiro Corrêa; Juliano S. Leal; Paulo M. Bandarra; Fábio S. Guagnini; Djeison L. Raymundo; David Driemeier (Pesquisa Veterinária Brasileira, 2007)
Sinais clínicos e lesões característicos de intoxicação por monensina foram induzidos em búfalos dosados (1 dia) com 15, 10, 7,5 e 5mg/kg de monensina. Apenas os búfalos dosados com 2,5 (1 dia) e 1 mg/kg (7 dias) de monensina não morreram. Os sinais clínicos iniciaram cerca de 6 h após dosagem com monensina e incluíram apatia, anorexia, diarréia, sialorréia, fraqueza muscular, taquicardia, dificuldade locomotora, dispnéia, distensão da jugular, decúbito e morte. As dosagens de creatinina quinase (CK) dos búfalos aumentaram acentuadamente após dosagem com monensina. As alterações macroscópicas foram ascite, hidrotórax, hidropericárdio, cardiomegalia, hepatomegalia e áreas pálidas focais no miocárdio e nos músculos esqueléticos. Degeneração e necrose de miofibras foram os principais achados histopatológicos. Por outro lado, nenhuma evidência de doença, nem mesmo alteração nos níveis de CK, foram observados nos bovinos dosados com as mesmas dosagens de monensina, confirmando observações preliminares que esses animais são mais resistentes à monensina que os búfalos. Monensin is widely used as a feed additive to improve performance of livestock; however accidental poisoning by this ionophore compound has been reported in a number of animal species. Typical clinical signs and lesions of monensin poisoning were induced in water buffaloes dosed with single dosages of 15, 10, 7.5, and 5mg/kg of the compound. Only buffaloes dosed with 2.5 mg/kg (1 day) and 1mg/kg (7 days) survived. Clinical signs initiated about 6 h post-dosing and included apathy, anorexia, diarrhea, drooling, muscular weakness, locomotion disorders, dyspnea, tachycardia, jugular distension and pulse, recumbency and death. The creatine kinase (CK) levels were highly augmented in blood samples of buffaloes dosed with monensin. Most prominent gross changes were ascites, hydrothorax, hydropericardium, cardiomegaly, hepatomegaly, and focal pale areas in the myocardium and in skeletal muscles. Degeneration and necrosis of myofibers were the principal histopathological findings. Conversely, no evidence of disease, neither change in CK levels were observed in the beef cattle steers dosed with same doses, confirming preliminary findings that buffaloes are more susceptible to monensin than cattle. In addition, this communication presents the minimal toxic dosage of monensin to buffaloes and suggests that CK tests may serve as health monitoring tools in the management of buffalo herds supplemented with monensin.